Diagnosing high-grade pancreatic intraepithelial neoplasia in surgically altered anatomy using pancreatic juice cytology - Soma Fukuda, MD; Susumu Hijioka, MD, PhD; Kohei Okamoto, MD; Shin Yagi, MD; Mark Chatto, MD; Yutaka Saito, MD, PhD; Takuji Okusaka, MD, PhD (VideoGIE)
Background and Aims: Diagnosing early-stage pancreatic ductal adenocarcinoma, particularly high-grade pancreatic intraepithelial neoplasia (HG-PanIN), remains challenging. Serial pancreatic juice aspiration cytologic examination (SPACE) using an endoscopic nasopancreatic drainage tube has demonstrated high diagnostic accuracy, but its application in surgically altered anatomy is technically demanding. We present a case in which balloon enteroscopy-assisted SPACE led to the diagnosis of HG-PanIN and successful resection. Methods: A 70-year-old man with a history of distal gastrectomy and Roux-en-Y reconstruction for gastric cancer underwent follow-up imaging, which revealed localized main pancreatic duct (MPD) stricture and parenchymal atrophy in the pancreatic tail. EUS identified a faint hypoechoic area around the stricture, but no distinct mass. EUS-guided tissue acquisition was inconclusive. Double-balloon enteroscopy-assisted endoscopic retrograde pancreatography was performed, revealing MPD stricture and distal dilation. A 5F endoscopic nasopancreatic drainage tube was placed across the stricture, and SPACE was conducted. Results: Twelve pancreatic juice cytology samples were aspirated every 2 to 3 hours over 3 days, each exceeding 1 mL. One sample (10th) was classified as Class IV, “suspicious for adenocarcinoma,” with cytology revealing nuclear enlargement and atypia. The patient was diagnosed preoperatively with pancreatic cancer (TisN0M0 stage 0) and underwent distal pancreatectomy without neoadjuvant chemotherapy. Pathology confirmed HG-PanIN of the MPD. The patient had no postoperative adverse events and remained recurrence-free at the 9-month follow-up. Conclusions: This case highlights the effectiveness of balloon enteroscopy-assisted SPACE in diagnosing HG-PanIN in surgically altered anatomy. However, given the relatively high risk of pancreatitis, SPACE should be reserved for patients with imaging or clinical findings suggestive of malignancy. By overcoming technical obstacles, this method offers a promising diagnostic strategy for early-stage pancreatic ductal adenocarcinoma in surgically altered anatomy.